Betul Saf Solat: Game of Common Mistakes in Saf Solat / Muhammad Nurhazim Haridan ... [et al.] - Haridan, Muhammad Nurhazim; Mohd Radzi, Muhammad Hamiz; Saman, Fadhlina Izzah; Che Haron, Mohammad Bakri (2021)
Covid-19 pandemic hits us all with new normal being practiced. As to control the virus from spreading, all religious activities are advised to be done at home including Muslim Prayers. Muslim prayers also known as Solat is a form of meditation, and Muslims are asked to pray five times a day at specific times of the day. The term of the prayer is, it must meet and obey all the precepts of the prayer and if one of the conditions is not fulfilled, then the prayer is invalid. As we need to learn the correct way to perform Solat in our own home, valid resources can be referred such as in books, articles, and journals, but mostly, people will search it online by browsing the official religion department websites. However, most information in official religious websites is in text-based approach which are not suitable for some readers with shortcomings primarily in higher-level systems as they have trouble to understand if there is too much text-related information. To tackle the problem, interactive learning material ‘Betul Saf Solat’ game is designed and developed by following the steps in Game Development Life Cycle (GDLC) methodology. Elements of gamification is applied where user can choose the right course of action for 11 levels in Saf Solat. Every mistake made by the players will trigger the explanation of the correct action needed to make they learn about the mistake is placing the Saf Solat for the characters designed in the game. The game is then evaluated through System Usability Scale (SUS) model. The result of the evaluation shows that 88.75% of respondents found the game is usable. Hence, it can be concluded that the objectives are all achieved, and it is hoped that more mistakes in Solat can be added as game features to make it comprehensive rather than only Saf Solat is being focused on.